Propriedades químicas e físicas do material particulado atmosférico e seus efeitos no crescimento de partículas - Silva, Leticia Caetano da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Aerosols are suspended solid or liquid species and / or airborne, with an average diameter of the nano or micron order. Aerosols can modify the atmosphere of the planet, affect the health of living beings, change the visibility and even the weather and availability of drinking water. These facts justify the need to improve the knowledge about their physical and chemical characteristics. Rapid changes in the amount and composition of aerosols in the atmosphere are the result of human activities, which are increasing as a result of economic expansion. Outside urban centers , the activities related to agribusiness are responsible for much of the emission of aerosols. The region of the center - west of São Paulo is distinguished by large area for sugar cane crop. Significant part still uses the of straw burning to facilitate the manual harvesting. The present study describes the chemical and physical characterization of atmospheric particulate matter in the state of São Paulo in the period from May 2010 to February 2012. The largest number of samples was collected in the central region of the state, the city of Araraquara, UNESP at the Campus, located southwest of the urban area. Other samples were collected southwest of the state , in the Ourinhos city, at the campus of UNESP, located 5 km from the city center. Together the campaign participated different research groups. To collect the aerosol was used Teflon filters and flow sampling ≈ 9 L min-1. This procedure allowed the collection of total suspended particulate matter. In the collected samples were determined water soluble ionic species by ion chromatography (NH4+, Na+, K+ , Mg2+ , Ca2+ , Cl- , NO3- , SO42- , PO43- , C2O42-). Equipment used did not enabled the separation of organic species acetate and formate, shown here as the summation of these organic anions ( H3CCOO- + HCOO-). In parallel directly measurements were performed to get the number concentration of particles...

Aerossóis são espécies sólidas ou líquidas suspendidas e/ou transportadas pelo ar, com diâmetro médio da ordem nano ou micrométrica. Os aerossóis podem modificar a atmosfera do planeta, afetar a saúde dos seres vivos, alterar a visibilidade e até mesmo o clima e a disponibilidade de água potável. Estes fatos justificam a necessidade de melhorar o conhecimento sobre suas características físicas e químicas. As rápidas mudanças na quantidade e composição dos aerossóis na atmosfera são resultados de atividades antrópicas que estão se intensificando como resultado de expansão econômica. Fora dos centros urbanos, as atividades relacionadas ao agronegócio são responsáveis por grande parte da emissão dos aerossóis. A região do centro-oeste paulista destaca-se pela grande área destinada à plantação de cana-de-açúcar. Parte significativa ainda utiliza a queima da palha para facilitação da colheita manual. O presente estudo descreve a caracterização química e física do material particulado atmosférico no interior do estado de São Paulo no período entre Maio de 2010 a Fevereiro de 2012. O maior número de amostras foi coletada na região central do estado, no município de Araraquara, dentro do Campus da Unesp, localizado a sudoeste da área urbana. Outras amostras foram coletadas a sudoeste do Estado, no município de Ourinhos, no Campus da UNESP, localizado a 5 km do centro urbano Nesta campanha participaram diferentes grupos de pesquisa. Para a coleta do aerossol utilizou-se filtros de Teflon e vazão de amostragem de ≈9 L min-1. Este procedimento possibilitou a coleta do material particulado suspenso total. Nas amostras coletadas foram determinadas as espécies iônicas solúveis em água por cromatografia de íons (NH4+, Na+, K+, Mg2+, Ca2+, Cl-, NO3-, SO42-, PO43-, C2O42-. O equipamento utilizado não permitiu a separação das espécies orgânicas acetato e formiato, apresentadas aqui como a somatórias...
Keywords: Quimica analitica; Atmosfera; Aerossois; Mudanças climaticas; Aerosols